Brand Extension Evaluation: an experimental research study in the service sector - Pimenta, Renato Ferreira; Lopes, Evandro Luiz; Silva, Dirceu da; Serralvo, Francisco Antonio (Review of Business Management, 2014)
This study analyzed the effects, in consumers’ evaluations, of different brand names (arbitrary, descriptive, and suggestive), of perceived similarities (high vs. low) and of perceived quality regarding brand extension in services. We implemented two experiments involving 1,338 respondents. In Experiment 1, by means of MANOVA, we managed to detect significant effects of brand names and of similarities in Attitude and Intention to Use of consumers. In Experiment 2, we added manipulation of perceived quality to the sample. We identified transfer of perceived quality to extended service, and that perceived quality overweighed effects of similarity and brand names in extensions, which indicates that perceived quality is more relevant in evaluation of brand extension in service when brand names are not recognized by consumers.